Decreased Km to dNTPs is an essential M-MuLV reverse transcriptase adoption required to perform efficient cDNA synthesis in One-Step RT-PCR assay. Issue 3 (15th March 2018) - Palikša, S; Alzbutas, G; Skirgaila, R
Abstract: Personalized medicine and advanced diagnostic tools based on RNA analysis are focusing on fast and direct One-Step RT-PCR assays. First strand complementary DNA (cDNA) synthesized by the reverse transcriptase (RT) is exponentially amplified in the end-point or real-time PCR. Even a minor discrepancy in PCR conditions would result in big deviations during the data analysis. Thus, One-Step RT-PCR composition is typically based on the PCR buffer. In this study, we have used compartmentalized ribosome display technique for in vitro evolution of the Moloney Murine Leukemia Virus reverse transcriptase (M-MuLV RT) that would be able to perform efficient full-length cDNA synthesis in PCR buffer optimized for Thermus aquaticus DNA polymerase. The most frequent mutations found in a selected library were analyzed. Aside from the mutations, which switch off RNase H activity of RT and are beneficial for the full-length cDNA synthesis, we have identified several mutations in the active center of the enzyme (Q221R and V223A/M), which result in 4–5-fold decrease of K m for dNTPs (<0.2 mM). The selected mutations are in surprising agreement with the natural evolution process because they transformed the active center from the oncoretroviral M-MuLV RT-type to the lenitiviral enzyme-type. We believe that this was the major and essential phenotypic adjustment required to perform fast and efficient cDNA synthesis in PCR buffer at 0.2-mM concentration of each dNTP.